How population and energy price affect China's environmental pollution?. (June 2019) - Li, Kunming; Fang, Liting; He, Lerong
Abstract: This paper examines the impact of population and energy price on China's environmental pollution through both industrial and residential channels. Our theoretical models reveal that the influences of population on environmental pollution are contingent on wage stickiness and wage elasticity. We also predict that environment pollution decreases with rising energy price, but downward energy price distortion intensifies environmental pollution. We test these hypotheses using panel data of 30 Chinese provinces from 2001 to 2016 and employing both constant coefficient and time-varying coefficient panel data models to conduct analyses. Our empirical results show that population growth, increased urbanization, and energy price distortion all intensify environmental pollution, while population aging and rising energy price tend to alleviate environmental pollution. Our results also reveal significant regional and time heterogeneity on the impact of population factors and energy price on China's environmental pollution. Highlights: The impact of population factors and energy price on environment pollution. A theoretical model analyzing determinants of industrial and residential pollution. An empirical test using Chinese provincial panel data. Pollution increases with population size and urbanization ratio. Pollution declines with energy price but increases with price distortion.